The Synergy Between Natural and Legal Law in Eco-ethics Context - Maior, Corneliu; Berlingher, Daniel; Dărău, Petru Aurel; Boja, Nicușor (Journal of Legal Studies, 2021)
From the multiple theses of eco-ethics, the study debates the complex relation between ethics – ethical principles and law – legislation in the field of environmental protection and durable development. Considering the differential – but also common – characteristics between natural laws and juridical ones that have an ecological signification, legislators must pass any law project while considering the needs of natural biosystems.